Preparation and characterization of CuO catalyst for the thermolysis treatment of distillery wastewater. Issue 20 (18th October 2018) - Sharma, Deepak; Prajapati, Abhinesh Kumar; Choudhary, Rumi; Kaushal, Rajesh Kumar; Pal, Dharm; Sawarkar, Ashish N.
ABSTRACT: CuO catalyst was prepared from copper sulfate by alkali precipitation method followed by drying and calcination. Characterization of CuO catalyst using X-ray diffraction, Brunauer–Emmett–Teller, and Barrett–Joyner–Halenda surface area analysis envisaged the effectiveness of CuO as a catalyst for the treatment of biodigester effluent (BDE) emanated from distilleries. The catalytic thermolysis is an efficient advance treatment method for distillery biodigester effluent (BDE). CT treatment of BDE was carried out in a 0.5 dm 3 thermolytic batch reactor using CuO as a catalyst at different pH (1–9), temperatures (80–110°C), and catalyst loadings (1–4 kg/m 3 ). With CuO catalyst, a temperature of 110°C, catalyst loading of 4 kg/m 3, and pH of 2 was found to be optimal, providing a maximum reduction in chemical oxygen demand of 65%. The settling characteristics at different temperatures of CT-treated sludge were also presented.